Decreased granzyme-B expression in CD11c+CD8+ T cells associated with disease progression in patients with HBV-related hepatocellular carcinoma - Gao, Lin; Hong, Zhixian; Lei, Guanglin; Guo, An-Liang; Wang, Fu-Sheng; Jiao, Yan-Mei; Fu, Junliang (Frontiers in Immunology, 2023)
Introduction CD11c+CD8+ T cells are an unconventional CD8+ T cell subset that exerts antiviral activity in infectious diseases. However, its characteristics in hepatocellular carcinoma (HCC) have not been elucidated. Methods Twenty-six patients with hepatitis B virus (HBV)-related HCC and 25 healthy controls (HC) were enrolled. The frequency and phenotype of CD11c+CD8+ T cells in peripheral blood and tumors in situ were detected by flow cytometry and immunohistochemistry. Results Both the HCC group and HC group had similar frequency and phenotype characteristics of CD11c+CD8+ T cells in the periphery. CD11c+CD8+ T cells were mainly composed of effector T cells, most of which were CD45RA+CCR7-. Compared with CD11c-CD8+ T cells, CD11c+CD8+ T cells had a higher proportion of CD38 and HLA-DR double positive, and expressed high levels of granzyme-B (GB) and degranulation marker CD107a, and produced high levels of interleukin-2 (IL-2), tumor necrosis factor alpha (TNF-α) and interferon-gamma (IFN-γ). However, the ability of degranulation and TNF-α production of CD11c+CD8+ T cells in patients with HCC were significantly lower than that in healthy controls. The GB expression level of peripheral CD11c+CD8+ T cells in patients with advanced stage of HCC was significantly lower than that in patients with early stage of HCC, and the GB expression level of liver-infiltrating CD11c+CD8+ T cells in tumor tissues was lower than that in non-tumor tissues. More importantly, the GB expression level of peripheral CD11c+CD8+ T cells was negatively correlated with tumor volume. Conclusions These findings indicate that CD11c+CD8+ T cells may have potential anti-tumor activity and that GB+CD11c+CD8+ T cells are associated with disease progression in patients with HBV-related HCC.